Saving the old apple tree: a book about caring for the environment (Educational Technologies Ltd Place of publication not identified, 2004)
"Saving the Old Apple Tree: A Book About Caring for the Environment" follows a group of children who discover that a beloved old apple tree in their neighborhood is in danger of being cut down. As they learn about the tree's importance to the local ecosystem and the memories it holds, the children rally together to save it. Through teamwork and creative thinking, they raise awareness in their community about the value of nature and the need for environmental stewardship. The story emphasizes the importance of caring for our planet and inspires young readers to take action in protecting their environment for future generations.